The Truth of Change - Elizabeth House; Quebec Writers' Federation (QWF) (2012)
Number of pages: 36

It's Raining Ducks (If You Know What I Mean) ;) - Vanguard Intercultural School; Quebec Writers' Federation (QWF) (2012)
Number of pages: 21

Super Ultra Mega Vanguard Poetry Book - Vanguard Intercultural School; Quebec Writers' Federation (QWF) (2012)
Number of pages: 21

Community Portrait : Sept-Îles - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2012)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.

Housing in Notre-Dame-de-Grace : A Portrait of the Issues, Resources and Services Affecting the Community - Pero, Bonnie (NDG Community Council (NDGCC), 2012)

The Thirty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2012)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2012)
Parallel title: Get Involved - Education Matters

Declaration from the Community Priority Setting Conference of the English-Speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2012)

Annual Report : 2011-2012 - 4Korners (2012)

Strategic Plan 2012-2017 - Coasters Association (2012)
The Lower North Shore of Québec stretches from Blanc Sablon (at the Labrador border) to Kegaska (opposite the eastern tip of Anticosti Island). Sixteen (16) communities, including the two (2) native communities of Pakua Shipi and Uanamen Shipu, are spread along 400 kilometres of rugged coastline, and in most cases are accessible only by boat, plane or snowmobile (in winter). Due to the vastness and isolation of the region, transportation costs are extremely high and often unreliable due to extreme weather conditions. This remote region, which is majority English-speaking, has witnessed a significant decline in population over the last few decades due to the collapse of the region’s main economic activity (the cod & salmon fishery), and the decline in the snow crab fishery. It is estimated that approximately half of the region’s adult population leaves the Coast at some time during the year to secure employment elsewhere. Many leave the territory for several months at a time while their family remains on the Lower North Shore which results in social dislocation as, in some cases, both parents leave for work and their children are housed with grandparents or other family members. Many social challenges have emerged from the changing circumstances, such as caring for the elderly, and many youth leave and do not return due to the lack of job opportunities.

Creativity : Insights, Directions, and Possibilities - Leading English Education and Resource Network (LEARN) (2012)
Number of pages: 510

Informal Learning : Flexible Contexts and Diverse Dimensions - Leading English Education and Resource Network (LEARN) (2012)
Number of pages: 340

Annual Report : 2011–2012 - NDG Community Council (NDGCC) (2012)

Rapport annuel : 2011–2012 - NDG Community Council (NDGCC) (2012)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2012)
Keywords: Official Language Minority Community (OLMC)

Annual Report : 2011-2012 - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)

Rapport Annuel : 2011-2012 - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)

Annual Report 2011-2012 - Voice of English-speaking Quebec (VEQ) (2012)